TESTING THE CHLOROFERT 48% Ec IN CONTROLLINGTHE WHITE FLY Aleuroclava Jasmine TAKAHASHI(HOMOPTERA: ALEYRODIDAE) UNDER LABORATORYAND FIELD CONDITION - AL-Seria, M. (Iraqi Journal of Science, 2024)
The efficacy chlorofert 48% Ec under field and laboratory condition at 0.5, 1.0and 1.5 on eggs, nymphs and adults of Aleuroclava Jasmine was investigated inBaghdad region. the result of laboratory show the insecticide give killing percentage100% on adults after one day from treatment at 0.5 with efficacy 100% and the highkilling percentage on nymphs and eggs after one weak from treatment the killingpercentage on nymphs 95.3 with efficacy 87.00 at 0.5 and on eggs the killingpercentage 61.25 with efficacy 78.00 at 0.5 the result in filed show the high killing percentage after one weak treatment, 1.5 gave 97 killing percentage with efficacy95% on eggs and 96% killing percentage with efficacy 95 on nymphs .the resultshow the number of live adults after one day from treatment at 0.5 gave 7.9, 1.0gave 15.1 and 1.5 gave 7.1 and after three day from treatment 0.5 gave 13.1, 1.0gave 7.9 and 1.5 gave 7.9 and these results show the number of adults decrease afterone weak from treatment at 0.5 gave 12.7, 1.0 gave 5.7 and 1.5 gave 5.1 and thehigh efficacy 80.8 at 1.5 after one weak from treatment.